Modified QuEChERS Based on Mixed Adsorbent Cleanup of Mycotoxins in Corn - Liyuan Zhang; Anna Dai; Runzhong Yu; Lili Qian (Journal of Chemistry)
In order to analyze the mycotoxins in corn, the modified QuEChERS high-performance liquid chromatography was applied to extract, clean up, and detect mycotoxins in a nonpolar system. The impurities such as fat and protein were removed from the corn sample, and the impurities in the sample solution have almost no effect on extraction efficiency. The proposed method leads to a greater choice of mycotoxin-extraction solvents in high-fat-solid samples. An appropriate extraction solvent was selected, the pretreatment conditions were optimized, and the extraction and cleanup of mycotoxins in high-fat solids were enhanced. By changing the experiment parameters, this method can be further used for the extraction and analysis of mycotoxins in complex samples (nonfat, low-fat, or high-fat). This method achieves good linearity in the range of 2.5–1000 μg/kg with the correlation coefficients for all analytes in the range of 0.9975 to 0.9989. The acceptable standard deviations for intraday and interday precision were 1.8–4.3% and 3.2–5.2%, respectively, with recoveries from 89.7 to 105.9%.